SELF-EFFICACY SCALE FOR PRIMARY SCHOOL TEACHERS IN ENGLISH LESSONS: A SCALE DEVELOPMENT STUDY - Bozkurt, Eyup; Aldim, Umit Ferit; Gecmez, Sevda (Escola Superior Dom Helder Camara, 2025)
The aim of this study is to develop a valid and reliable measurement instrument to assess the self-efficacy levels of classroom teachers in English language teaching. The study sample consists of classroom teachers working in Elaz & imath;& gbreve;, T & uuml;rkiye, in 2024. The study was conducted in two phases. In the first phase, 257 classroom teachers participated in the Exploratory Factor Analysis (EFA), while in the second phase, 253 classroom teachers took part in the Confirmatory Factor Analysis (CFA), resulting in a total of 510 participants. To develop the scale, a comprehensive review of the relevant literature was conducted, and an initial pool of 29 items was generated. Based on the evaluations of two field experts and one English language expert, four items were removed. Additionally, three items were eliminated due to language and expression concerns following expert feedback. As a result of the EFA, two items with overlapping or low factor loadings were excluded. The EFA findings revealed a three-factor structure. Subsequently, CFA was performed to validate this structure. After making the necessary adjustments to achieve acceptable goodness-of-fit indices, the scale was confirmed to have strong and acceptable fit values. Furthermore, the overall Cronbach's Alpha reliability coefficient was calculated as .976. Following these analyses, the final 20-item, three-factor scale was determined to be a valid and reliable instrument, suitable for use in the field, and was introduced into the literature.
Keywords: Self-efficacy; Classroom Teacher; Scale Development; English Language Teaching